Using Harvest Slot Limits to Promote Stock Recovery and Broaden Age Structure in Marine Recreational Fisheries: A Case Study. (15th December 2020) - Kasper, Jacob M.; Brust, Jeffrey; Caskenette, Amanda; McNamee, Jason; Vokoun, Jason C.; Schultz, Eric T.
Abstract: Fish populations with broad age distributions are expected to have higher reproductive capacity than age‐truncated populations because of the disproportionate contributions of older fish. Harvest slot limits, an expected means of ameliorating age truncation, are modeled for Tautog Tautoga onitis in an overfished population subunit that is experiencing overfishing. Tautog, currently managed with a 40‐cm minimum size limit (MSL), is a candidate species for slots because it is relatively long‐lived and slow‐growing, with low discard mortality. We evaluated changes in biomass and abundance at age relative to management with the current MSL regulations using a forward population simulation model for four slots: 35–45 cm (small–wide), 38–42 cm (small–narrow), 40–50 cm (large–wide), and 43–47 cm (large‐narrow), inclusive of lower and upper length limits. Angler behavioral responses were evaluated at 0, 10, and 20% noncompliance with the upper slot limit. The biomass and number of fish removed were reduced with harvest slot limit management relative to the MSL, but because the harvest was redirected to smaller fish the reduction in numbers removed was not as large as the reduction in biomass removed. Slot limits broadened the age structure within 10 years by reducing fishing mortality on extant fish. Median spawning stock biomass (SSB) recovered more quickly in three of the slots than with MSL regulation (3–6 years to reach SSB associated with a fishing mortality that yields 30% spawners per recruit as compared to 9 years with MSL management). We concluded that harvest slot limits can broaden age structure and restore biomass in overfished fisheries, but they should be evaluated when managing coastal fisheries as a reduction in biomass removed is required.